Fungsi, Kategori, dan Peran Sintaksis Menggunakan Teori RRG dalam Acara “Indonesia Lowyers Club” - Atika Gusriani; Zherry Putria Yanti; Yuniarti, Lisa (LP. Ma'arif Janggan Magetan, 2022)
The predicate is a determining element in a sentence. Sentences that are not clearly structured, result in the sentence being ineffective. This of course results in incomplete functions, categories, and roles in a sentence, making it difficult to understand. The purpose of this research is to describe functions, categories, and syntactic roles using the theory of Role and Reference Grammar (RRG) in the